Physical chitosan microhydrogels as scaffolds for spinal cord injury restoration and axon regeneration. (September 2017) - Chedly, Jamila; Soares, Sylvia; Montembault, Alexandra; von Boxberg, Ysander; Veron-Ravaille, Michèle; Mouffle, Christine; Benassy, Marie-Noelle; Taxi, Jacques; David, Laurent; Nothias, Fatiha
Abstract: Recovery from traumatic spinal cord injury (SCI) usually fails due to a cascade of cellular and molecular events that compromise neural tissue reconstitution by giving rise to glial scarring and cavity formation. We designed a scaffold material for SCI treatment containing only chitosan and water as fragmented physical hydrogel suspension (Chitosan-FPHS), with defined degree of acetylation (DA), polymer concentration, and mean fragment size. Implantation of Chitosan-FPHS alone into rat spinal cord immediately after a bilateral dorsal hemisection promoted reconstitution of spinal tissue and vasculature, and diminished fibrous glial scarring: with astrocyte processes primarily oriented towards the lesion, the border between lesion site and intact tissue became permissive for regrowth of numerous axons into, and for some even beyond the lesion site. Growing axons were myelinated or ensheathed by endogenous Schwann cells that migrated into the lesion site and whose survival was prolonged. Interestingly, Chitosan-FPHS also modulated the inflammatory response, and we suggest that this might contribute to tissue repair. Finally, this structural remodeling was associated with significant, long-lasting gain in locomotor function recovery. Because it effectively induces neural tissue repair, Chitosan-FPHS biomaterial may be a promising new approach to treat SCI, and a suitable substrate to combine with other strategies.